Impact of Surfactant Therapy on Preterm Neonates: A Meta-Analysis Evaluating Respiratory and Hemodynamic Outcomes - Ayudimartini, Ni Luh (Scientific Journal of Pediatrics, 2025)
Introduction: Surfactant deficiency is a major contributor to neonatal respiratory distress syndrome (RDS) in preterm infants. Surfactant replacement therapy has become a cornerstone in managing RDS, but its impact on broader respiratory and hemodynamic outcomes remains an area of active investigation. This meta-analysis aimed to comprehensively evaluate the effects of surfactant therapy on preterm neonates, encompassing both respiratory and hemodynamic parameters. Methods: A systematic search of electronic databases (PubMed, Embase, Cochrane Library) was conducted to identify randomized controlled trials (RCTs) and observational studies evaluating surfactant therapy in preterm neonates. Studies reporting on respiratory outcomes (need for mechanical ventilation, duration of ventilation, oxygen requirement) and hemodynamic outcomes (patent ductus arteriosus (PDA) incidence, blood pressure, cerebral blood flow) were included. Data extraction and quality assessment were performed independently by two reviewers. Meta-analyses were conducted using random-effects models. Results: A total of 35 studies (22 RCTs, 13 observational studies) involving 4,875 preterm neonates were included. Surfactant therapy was associated with a significant reduction in the need for mechanical ventilation (RR 0.72, 95% CI 0.65-0.80, p<0.001), duration of mechanical ventilation (MD -1.8 days, 95% CI -2.5 to -1.1, p<0.001), and oxygen requirement (MD -5%, 95% CI -7 to -3, p<0.001). A trend towards reduced incidence of PDA was observed (RR 0.85, 95% CI 0.71-1.02, p=0.08). Surfactant therapy also led to improvements in blood pressure parameters and cerebral blood flow. Conclusion: Surfactant therapy in preterm neonates confers significant benefits in respiratory outcomes, including reduced need for and duration of mechanical ventilation, and decreased oxygen requirement. A potential beneficial effect on PDA incidence warrants further investigation. These findings underscore the critical role of surfactant therapy in improving the respiratory and hemodynamic status of preterm neonates.